Wnt/β-catenin signaling is an evolutionarily conserved determinant of chordate dorsal organizer - Kozmikova, Iryna; Kozmik, Zbynek (eLife, 2020)
Deciphering the mechanisms of axis formation in amphioxus is a key step to understanding the evolution of chordate body plan. The current view is that Nodal signaling is the only factor promoting the dorsal axis specification in the amphioxus, whereas Wnt/β-catenin signaling plays no role in this process. Here, we re-examined the role of Wnt/βcatenin signaling in the dorsal/ventral patterning of amphioxus embryo. We demonstrated that the spatial activity of Wnt/β-catenin signaling is located in presumptive dorsal cells from cleavage to gastrula stage, and provided functional evidence that Wnt/β-catenin signaling is necessary for the specification of dorsal cell fate in a stage-dependent manner. Microinjection of Wnt8 and Wnt11 mRNA induced ectopic dorsal axis in neurulae and larvae. Finally, we demonstrated that Nodal and Wnt/β-catenin signaling cooperate to promote the dorsal-specific gene expression in amphioxus gastrula. Our study reveals high evolutionary conservation of dorsal organizer formation in the chordate lineage.
Keywords: Smad2 Protein; kopinatci; Humans; Nodal Protein; branchiostoma lanceolatum; beta-katenin; Lancelets; wnt/β-catenin signaling; Goosecoid Protein; protein Smad2; Biological Evolution; developmental biology; lidé; HEK293 Cells; zvířata; protein goosecoid; Wnt Signaling Pathway; axial patterning; evolutionary biology; body plan; signální dráha Wnt; protein nodal; biologická evoluce; HEK293 buňky; beta Catenin; Animals; branchiostoma floridae; evolution